ANALISIS PENGENDALIAN KUALITAS PROSES PRODUKSI PALETZING PADA PT DOELLKEN BINTAN - Alfian, Alfian Alfian; Susanti, Elva (Computer Science and Industrial Engineering, 2021)
Quality control is an important part of developing a company improvement strategy. PT Doellken Bintan is a manufacturing company producing palletzing. Based on the results of data processing using the Value Stream Mapping (VSM) method, the mapping of current mapping processes in the manufacturing production process is obtained so that the description of the process can be known and can be used as a reference base in designing the company's future map. In addition, controlling the quality of the palletzing production process results in the risk of failure on the results of the Failure Modes and Effects Analysis (FMEA) which is used as a priority for improvement proposals. For the greatest risk of failure on the FMEA RPN are those that have a Risk Priority Number (RPN) value above 100, namely Broken Screw, Old Barrel Cable, Short UV, Short Blower, Error Temperature Controller, Broken Air Valve, Roll Chain in the gear box it is loose, the printing knife is worn / out, the compressor is damaged, the utility error, the air hose is leaking, the wind pressure sensor is damaged. However, RPNs below 100 are also provided with a review of improvements that are adjusted to company conditions.